Analisis Keterampilan Literasi Digital di Kalangan Mahasiswa Universitas Nias : Tantangan dan Strategi Peningkatan - Darwis Setiawan Waruwu; Farida Maria Vinsensia Lahagu (CV. SINAR HOWUHOWU, 2024)
This research is an analysis of digital literacy skills among Nias University students, which focuses one the challenges faced and strategies for improving the quality of these skills. Digital literacy is very important in the increasingly digitalized world of education and work. However, some students in certain areas, including the Nias Islands, face many obstacles in accessing and mastering digital technology effectively and optimally. This research uses a qualitative descriptive approach with survey and interview methods in order to collect some data from a sample of Nias University students. Data analysis was carried out in order to identify the level of digital literacy skills, the challenges faced, and special needs that support improving these skills. In overcoming this challenge, research recommends several strategies, including providing more structured digital literacy training, increasing access to devices and the internet, and integrating digital literacy in the Nias University curriculum. Nias University is advised to collaborate with local governments and the private sector to provide adequate digital infrastructure. In this implementation strategy, it is hoped that digital literacy will increase and the need to prepare Nias University students to face the challenges of the world of work in the future after completing increasingly digital higher education. Therefore, this research provides very important insights for several stakeholders in the education and government sectors in designing several digital skills development policies and programs in regions that have limited access to information technology.